If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + -5) = 2(q + 5) Reorder the terms: 2(-5 + a) = 2(q + 5) (-5 * 2 + a * 2) = 2(q + 5) (-10 + 2a) = 2(q + 5) Reorder the terms: -10 + 2a = 2(5 + q) -10 + 2a = (5 * 2 + q * 2) -10 + 2a = (10 + 2q) Solving -10 + 2a = 10 + 2q Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2a = 10 + 10 + 2q Combine like terms: -10 + 10 = 0 0 + 2a = 10 + 10 + 2q 2a = 10 + 10 + 2q Combine like terms: 10 + 10 = 20 2a = 20 + 2q Divide each side by '2'. a = 10 + q Simplifying a = 10 + q
| -12-n=-10 | | (9y^2-6y+9)-(5y^2-6y+8)= | | 3(a-8)+7=5(a+2)-3a-19 | | 8x-6=130 | | -17-v=-5 | | -4x+8+12=44-48 | | 2(6-4d)=2s-9d | | 5=x-(-28) | | 2x-x-10=-13 | | -74=6+10x | | 14x+4=116 | | k-8=-15 | | 5y+15=80 | | 10n=-60 | | 7x+6=6x+18 | | 0=7-4y | | 24+3=3w | | -6=7-4y | | 4x+3y-3=15 | | 27x-3=34x | | 2(n+3)+3(n-1)= | | m+76.3=131.56 | | (2x-6)m=(x+3)m | | 16+31m=48+23m | | -16x^2+128x=240 | | x+104=95 | | 6=7-4y | | 7x=x+6x | | y^4+4y+x^4-6x^2=0 | | 2y+35=4 | | 8+14x=-8+16x | | -2(3)+5(3)=10 |